Health and wellbeing of people with intellectual disability in New South Wales, Australia: a data linkage cohort - Reppermund, Simone (BMJ Open, 2019)
PURPOSE: People with intellectual disability (ID) experience high rates of physical and mental health problems, while access to appropriate healthcare is often poor. This cohort was established to develop an epidemiological profile related to the health, health service use, disability services, mortality and corrective services records of people with ID. PARTICIPANTS: The cohort contains 92 542 people with ID (40% females) with a median age of 23 years (IQR: 12–43 years) and 2 004 475 people with a neuropsychiatric or developmental disorder diagnosis (50% females) with a median age of 51 years (IQR: 29–73 years) from New South Wales, Australia. The whole sample contains records for 2 097 017 individuals with most data sets spanning financial years 1 July 2001 to 30 June 2016. A wide range of data from linked population data sets are included in the areas of disability, health, corrective services and targeted specialist support services in public schools, Public Guardian and Ombudsman services. FINDINGS TO DATE: This study includes one of the largest cohorts of people with ID internationally. Our data have shown that the presence of ID is significantly associated with emergency department presentations and psychiatric readmissions after the first psychiatric admission based on a subcohort of people with a psychiatric admission. Adults with ID experience premature mortality and over-representation of potentially avoidable deaths compared with the general population. FUTURE PLANS: Within the health service system, we will examine different components, that is, inpatient, emergency adult services, children and younger people services and costs associated with healthcare as well as mortality, cause and predictors of death. The neuropsychiatric and developmental disorders comparison cohort allows comparisons of the physical health, mental health and service use profiles of people with ID and those with other neuropsychiatric disorders.